Rancang Bangun Sistem Pengelompokan Pelanggan Potensial Menggunakan Metode K-Means Untuk Promosi Paket Wisata (Studi Kasus PT. Bali Sinar Mentari) - Krisnawan, I Putu Agus Hendra; Sutanto, Teguh; Sutomo, Erwin (Jurnal JSIKA, 2012)
PT. Bali Sinar Mentari is a company engaged in the field of business travel services in Bali. In company like this, giving promotion is one of important factor in helping the sale of services to customers. The problem is managers have difficulty to determine which customers have the right to be given promotion. Based on that, company required system to classify the potential customer to be given promotions via email. clustering customers can use K-Means method. This method must use the physical data, not abstract, it is same with the data used in problems in grouping customers at PT. Bali Sinar Mentari. In this final project, the application of clustering system can be run in line with expectations. The process of clustering customers with the K-Means method can work well and generate groups of potential customers.   Keyword: clustering, potential customers, tourism package